FOXK1 Promotes Proliferation and Metastasis of Gallbladder Cancer by Activating AKT/mTOR Signaling Pathway - Wencong, Ma; Jinghan, Wang; Yong, Yu; Jianyang, Ao; Bin, Li; Qingbao, Cheng; Chen, Liu; Xiaoqing, Jiang (Frontiers in Oncology, 2020)
Gallbladder cancer (GBC) is one of the most lethal malignancies worldwide, with extremely poor prognosis. Recently, forkhead box k1 (FOXK1), a member of the FOX transcription factor family, has been reported to be correlated with tumor progression in multiple malignancies. However, the role of FOXK1 in GBC has not been elucidated. In this study, we demonstrated that the expression level of FOXK1 was elevated in human GBC tissues and associated with increased liver metastasis, poor histological differentiation, advanced TNM stage, and shorter overall survival. Knockdown of FOXK1 expression inhibited GBC cells proliferation and metastasis. Consistently, overexpression of FOXK1 promoted GBC cells progression. Mechanical investigations verified that knockdown of FOXK1 could lead to G1/S cell cycle arrest through downregulating CDK4, CDK6, cyclin D1, and cyclin E1. And FOXK1 could regulate the expression of epithelial–mesenchymal transition (EMT) related proteins E-cad, N-cad, and Vimentin. Moreover, we found that FOXK1 could regulate the activation of Akt/mTOR signaling pathway. In addition, AKT special inhibitor MK-2206 could abolish the proliferation and metastasis discrepancy between FOXK1 overexpression GBC cells and control cells, which suggested the tumorpromoting effect of FOXK1 may be partially related with the activations of Akt/mTOR signaling pathway. Collectively, our results suggested that FOXK1 promotes GBC cells progression and represent a novel prognostic biomarker and potential therapeutic target in GBC.